The mediation of self-efficacy between Antecedents and organisational citizenship Behaviour in the public sector / Meor Rashydan Abdullah - Meor Rashydan , Abdullah (2020)
Organisational citizenship behaviour (OCB) has become popular among scholars in organisational behaviour, psychology, and management studies since it significantly contributes to the success of an organisation. Organisational citizenship behaviour plays an important role in organisational settings for its effectiveness and the efficiency of the services or operation provided. Empirical studies on OCB in recent years were mostly conducted in a Western context. However, there is a limit of providing extensive information and in-depth understanding of employee’s citizenship behaviour in Malaysia settings. This study attempts to narrow the gap in the past literature. In the public sector, OCB is highly valued and critical in enhancing the performance of a government organisation. Organisational citizenship behaviour plays a significant role by encouraging employees to respond effectively to the changing environment and at the same time be able to deliver high-quality services. However, there is little empirical research on OCB in the public sector and the applicability of the resource perspective from the theory of conservation of resource in measuring employee’s citizenship behaviour. This study utilises the conservation of resource theory in an effort to provide evidence on the effect of individual and organisational factors towards employees’ citizenship behaviours thus extending the application of conservation of resource (COR) theory on the effect of personal resource as a mediator. Specifically, this study looks at individual factors such as distinguished work-family conflict (work-FC) and family-work conflict (family-WC) and an organisational factor such as supervisory support as independent variables that may have an effect on citizenship behaviour. Furthermore, this study attempts to investigate the role of self-efficacy as a mediating variable on those relationships. Using a survey data of 618 public administrators from four government organisations located in Putrajaya, Malaysia, the conservation of resource theory was tested using statistical analysis SPSS and Structural Equation Modelling - Partial Least Square (Version 3.0). It was found that self-efficacy mediates the relationship between supervisory support and OCB as well as between family-WC and OCB. In contrast, self-efficacy does not mediate the relationship between work-FC and OCB. The findings illustrate the effect of selfefficacy as a personal resource that contributes to the resource’s loss and resource gain, which influence employees’ citizenship behaviour. In addition, self-efficacy and supervisory support were found to be a notable predictor of citizenship behaviour, a finding that corresponds to the past studies which denote that individual self-belief and supportive supervisory within an organisation is a predictor of individual citizenship behaviour. The results suggest that an organisation should focus on developing individual characteristics to foster self-belief and to promote a supportive working environment, the purpose being to enhance employees’ engagement in the organisation. The findings of this study can supplement the existing literature and open new avenues for future research.